Legal Protection For Creditors Who Hold Credit Rights Where The Sales Value Of The Collateral Is Smaller Than The Debt Of The Bankrupt Debtor Based On Law No. 37 Of 2004 Concerning Bankruptcy And Pkpu - Simanjuntak, Baginta; Nababan, Roida; Habeahan, Besty (Dinasti Research, 2025)
The dynamic growth of business activities in Indonesia has increased debt–credit transactions, which can lead to disputes when debtors fail to meet obligations, particularly in bankruptcy. Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations provides a framework for asset settlement and protection for secured creditors (separatist creditors). However, issues arise when the collateral’s execution value is insufficient to cover the debtor’s total debt, leaving a shortfall unpaid. This study examines the legal protection for separatist creditors in such cases and remedies available when the curator fails to pay the remaining debt. Using a normative juridical method with statutory and conceptual approaches, the research is based on primary, secondary, and tertiary legal materials analyzed qualitatively. The findings show that the Bankruptcy Law does not clearly regulate the procedure for claiming such shortfalls, creating legal uncertainty and inconsistent commercial court practices. The study concludes that the law should be reformed to expressly allow the shortfall to be claimed as a concurrent debt and that the Supreme Court should issue guidelines to ensure consistent interpretation and strengthen legal protection for separatist creditors.